Approach of Processes for the Distribution of Economic Resources in Public University of Ecuador - Mora, MÃƒÂ³nica Murillo; Espinosa, Maricela Reyes; Delgado, Myrna Ricard (International Research Journal of Management, IT & Social Sciences, 2018)
The objective of the study was to analyze the process approach in the context of university management, applied to the economic and financial process, as a contribution to the fulfillment of the criteria of the formula of distribution of resources for the Ecuadorian Higher Education Institutions, describing the criteria and parameters based on current regulations. The research that was developed is empirical, descriptive in scope, using as methods, historical logic, analysis, and synthesis of the documentary sources linked to the study object, induction - deduction and mapping for the graphical representation of the information collected. The results allow identifying that the Ecuadorian public universities as of 2013 have an instrument that weighs the quality of the distribution of resources.